Multilingualism in An ESP Online Learning Class A Case in An English For Professional Course - Melania Wiannastiti (Prodi Sastra Inggris UKI, 2022)
ESP (English for Specific Purposes) in online learning classes has its way of communicating since the students do not meet physically because they only meet virtually. The study aims to find out the languages used among the online learning students in an ESP online classroom, especially in interacting and communicating with one another in a team and virtual classroom, and to figure out the students’ attitude toward multilingualism in ESP online classroom communication. A questionnaire is distributed to 24 students joining an English for Professional class at BINUS Online Learning as the participants. The data from the questionnaire is analyzed qualitatively in the form of percentages. The result shows that the students apply multilingualism in the online learning class for interaction and communication. They show both positive and negative attitudes toward the use of many languages in their team and classroom communication while English is required as the means of communication and interaction in the team and classroom.